The Contribution of CFNI to Caribbean development 2001 - 2010 (CFNI & PAHO KingstonJM, 2011)
Chronicles the achievements of the CFNI over the last decade and provides broad accountability of their technical cooperation mandate; an evaluation of efforts based on results; and critical insights into the complexity of implementing programmes on Food and Nutrition in the region.
Keywords: CFNI